2019
DOI: 10.1071/hc18097
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime prevalence of exostoses in New Zealand surfers

Abstract: INTRODUCTIONExternal auditory exostosis (EAE) is a benign, irreversible bony outgrowth that arises from the temporal bone. EAE projects into the external ear canal, potentially causing recurrent otitis externa and conductive hearing loss. AIMTo determine lifetime prevalence of EAE in New Zealand (NZ) surfers. METHODSThis study used an online national survey. RESULTSRespondents were 1376 NZ surfers (recreational = 868, competitive = 508). Mean surfing experience was 16.2 years. Most self-classified as advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…It is interesting to note that when we evaluated exostosis via survey, as opposed to otoscopic examination, we found a lifetime prevalence of only 3.5% in Australian surfers [26] and more recently [30] 28.9% in New Zealand surfers. Chaplin and Stewart [29] reported a lifetime prevalence of exostosis of 73.0% in New Zealand surfers, with one half presenting with a Grade 2 or Grade 3 severity.…”
Section: Lifetime Prevalence Of Exostosismentioning
confidence: 81%
“…It is interesting to note that when we evaluated exostosis via survey, as opposed to otoscopic examination, we found a lifetime prevalence of only 3.5% in Australian surfers [26] and more recently [30] 28.9% in New Zealand surfers. Chaplin and Stewart [29] reported a lifetime prevalence of exostosis of 73.0% in New Zealand surfers, with one half presenting with a Grade 2 or Grade 3 severity.…”
Section: Lifetime Prevalence Of Exostosismentioning
confidence: 81%
“…As a non-surfer, I have always thought that surfers must be exceptionally healthy people so I was surprised and interested to receive a paper about a particular health problem disproportionally affecting surfers (exostoses). 10 I hope readers will find this paper interesting also. Our other clinical paper uses a case-control approach to investigating the usefulness of dermoscopy in general practice surgical procedures.…”
Section: Aspirations Innovations and Realitymentioning
confidence: 85%
“…The other clinically-oriented papers in this issue relate to pneumococcal disease, 8 mental health, 9 exostoses in surfers, 10 and dermoscope-guided surgical procedures in general practice. 11 Descriptive epidemiology such as the approach presented in the article by Eichler et al 8 is sometimes regarded as rather pedestrian by our public health colleagues but for people working in primary healthcare and delivering vaccines it is both useful and reassuring to have access to this sort of analysis.…”
Section: Aspirations Innovations and Realitymentioning
confidence: 99%
“…Nathanson et al reported lower rates, with EAE and OE representing 7% and 14% of the total number of chronic injuries, respectively 26. More recently, studies in New Zealand and Ireland found EAE in 29% and 66% of surfers, respectively, and also demonstrated that EAE was correlated with increased hours spent surfing 52 53…”
Section: Overuse Conditionsmentioning
confidence: 99%